Analysis of metabolic differences in Tibetan medicinal plant Phlomoides rotata leaves in different habitats based on non-targeted metabolomics - Wang, Lele; Wang, Hongli; Chen, Junlin; Lamu, Yuzhen; Qi, Xiangyang; Lei, Lei; Mao, Kangshan; Tso, Sonam (Frontiers in Plant Science, 2025)
Phlomoides rotata, a traditional Tibetan medicinal herb renowned for its anti-inflammatory and analgesic properties, exhibits distinct metabolite profiles across heterogeneous environments. However, the impacts of altitude and slope orientation on its secondary metabolism remain poorly understood. This study aimed to characterize metabolite variations in the leaves of Phlomoides rotata under different elevations and microclimates, providing a mechanistic basis for its quality evaluation and sustainable utilization. Metabolomic analysis was conducted using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-MS). Leaf samples were collected from three altitude gradients (4,300 m, 4,600 m, 5,000 m) and two slope orientations (south vs. north) in Budanla Mountain, Qusong County, Shannan, Xizang Autonomous Region, China. A total of 2,331 metabolites were detected, with lipids (41.93%), organic oxygen compounds (13.95%), and phenylpropanoids (12.4%) dominating the profile. Altitudinal gradients induced significant changes in 5 differentially accumulated metabolites (DAMs), including procyanidin B2 and dihydrocoumarin. Slope orientation influenced 17 DAMs, such as 2,3-secoporrigenin and 2-O-α-D-galactopyranosyl-1-deoxynojirimycin. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed altitude-specific enrichment in flavonoid biosynthesis and pantothenate/CoA biosynthesis, while slope-related DAMs were enriched in glycerophospholipid metabolism and galactose metabolism. Altitude-driven increases in flavonoids (e.g., procyanidin B2) likely reflect adaptive responses to UV radiation and oxidative stress. Slope-related metabolite shifts, particularly glycerophospholipids, may relate to microclimate differences in temperature and moisture. These findings highlight the critical role of environmental factors in shaping the metabolic phenotype of Phlomoides rotata, with implications for pharmacologically active compound biosynthesis. The identified DAMs serve as potential biomarkers for quality control, while pathway analysis provides targets for metabolic engineering in conservation and cultivation practices.